Designing learning environments to promote student learning: Ergonomics in all but name. - Smith, Thomas J. (Work)
OBJECTIVE: This report introduces evidence for the conclusion that a common theme underlies almost all proposed solutions for improving the performance of K-12 students, namely their reliance on the design of educational system environments, features and operations. METHODS AND RESULTS: Two categories of design factors impacting such performance are addressed: (1) 9 factors reliably shown to have a strong influence - namely environmental design of classroom and building facilities, longer exposure to learning, cooperative learning designs, early childhood education, teaching quality, nutritional adequacy, participation in physical activity, good physical fitness, and school-community integration; and (2) 11 factors with an equivocal, varied or weak influence - classroom technology, online learning environments, smaller class size, school choice, school funding, school size, school start times, teacher training level, amount of homework, student self-confidence and informal learning. CONCLUSIONS: It is concluded that: (1) student learning outcomes, and more broadly the edifice of education itself, are largely defined in terms of an extensive system of design factors and conditions; (2) the time is long overdue for the educational system to acknowledge the central role of E/HF design as the major influence on student performance and learning; and (3) K-12 educators and administrators should emphasize allocation of resources to design factors reliably shown to have a strongly positive impact on student performance, but should treat expenditure on factors with equivocal, varied or weak influence on such performance with more caution and/or skepticism.